SCIENCE PRACTICUM ACTIVITIES THROUGH WATER AND AIR POLLUTION EXPERIMENTS ON ENVIRONMENTAL POLLUTION MATERIALS IN JUNIOR HIGH SCHOOLS - Laelandi, Rahayu; Sriyati, Siti; Prima, Eka Cahya (JOURNAL OF SCIENCE EDUCATION AND PRACTICE, 2023)
Learning that is carried out using the experimental practicum method gives students the ability to think critically, actively and collaboratively in solving a problem in science material, especially environmental pollution material. This study aims to provide an alternative way for educators to convey material related to environmental pollution, especially water and air pollution. The method used is the development of practicum learning methods on the material of water pollution and air pollution which is carried out in class 7th grade students at junior high school. The results of the water pollution practicum research stated that the average fish operculum movement experienced the highest decrease in Jar 3, from 95 to 69. The results of observations on the average movement of fish that experience slow changes and die the most are in Jar 2 with an average of 60% of fish moving slowly and 80% of fish dying in the second minute. The higher the dose of detergent, the less movement of the fish operculum and the slower the movement of fish and the death. In air pollution, the highest percentage decline in normal cricket activity was in Jar 2, from 50% in the 3rd minute to 30% in the 6th minute. The longer the crickets were exposed to the smoke of the mosquito coils, the lower the displacement of the places carried out by the crickets and the higher the activity move the antenna.